Potassium sodium niobate-based lead-free piezoelectric ceramic and method for manufacturing the same
Patent Information
- Application Number
- CN202410866704.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-07-01
AI Technical Summary
[0004]然而,KNN基无铅压电陶瓷在实际应用中仍面临制备工艺、性能调控等诸多问题
[0026] This invention relates to a potassium sodium niobate-based lead-free piezoelectric ceramic and its preparation method, wherein the general chemical formula of the potassium sodium niobate-based lead-free piezoelectric ceramic is 0.965K. 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where 0 < x ≤ 0.04. The potassium sodium niobate-based lead-free piezoelectric ceramic of this invention does not contain lead, making it an environmentally friendly material. Furthermore, this potassium sodium niobate-based lead-free piezoelectric ceramic possesses a high mechanical quality factor, a good piezoelectric constant, and low dielectric loss, thus having a wide range of applications. Finally, the preparation method of this invention is simple, stable, easy to operate, and suitable for industrial production.
Smart Images

Figure CN118851760B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of materials science and engineering, and in particular to a potassium sodium niobate-based lead-free piezoelectric ceramic and its preparation method. Background Technology
[0002] Piezoelectric ceramics are an important class of functional materials exhibiting the piezoelectric effect. Based on their electromechanical conversion properties and the acoustic, optical, and thermally sensitive properties generated through composite processes, piezoelectric ceramics have found applications in fields including information technology, optoelectronics, precision control technology, and non-destructive testing technology. Examples include piezoelectric resonators, piezoelectric buzzers, piezoelectric filters, piezoelectric transformers, piezoelectric loudspeakers, piezoelectric igniters, and piezoelectric motors. Furthermore, with the rapid development of next-generation information technology and artificial intelligence, their applications continue to expand.
[0003] The piezoelectric effect includes the direct piezoelectric effect and the inverse piezoelectric effect, which refer to the phenomena of generating electric charge under the action of force and deformation under the action of an electric field, respectively. Currently, the main materials used in the market are lead-based piezoelectric ceramics, represented by Pb(Zr,Ti)O3. However, due to their high lead oxide content, they pose serious harm to the environment and human health during production, use, and disposal. In recent years, with the increasing awareness of ecological and environmental protection and the implementation of social sustainable development strategies, the development of lead-free piezoelectric materials and devices has become an urgent task. Therefore, the research and development of high-performance lead-free piezoelectric ceramics is of great significance to electronic information technology, environmental protection, and sustainable development strategies. Perovskite-structured potassium sodium niobate ((K,Na)NbO3, abbreviated as KNN)-based lead-free piezoelectric ceramics, due to their excellent piezoelectric properties and high Curie temperature, are considered one of the promising candidate materials to replace lead-based piezoelectric ceramics. They have attracted widespread attention from researchers, who have conducted extensive research and achieved breakthroughs in component design, structural control, performance optimization, and novel properties.
[0004] However, KNN-based lead-free piezoelectric ceramics still face many challenges in practical applications, including fabrication processes and performance control. On the one hand, when using traditional solid-state methods to prepare materials, the volatilization of alkali metal elements K and Na during sintering makes it difficult to obtain KNN lead-free piezoelectric ceramics with high density and excellent performance. On the other hand, there is a lack of effective demand-oriented methods for controlling the performance of piezoelectric ceramics. The energy consumed by a piezoelectric body to overcome internal friction at resonance is represented by the mechanical quality factor Q. m Value characterization, different device applications affect Q m Different requirements are put forward. For example, in functional transducers such as step-up transformers, the Q of the material... m The voltage boost ratio is directly proportional to the voltage of the device, therefore these devices require a high Q. m Value; however, if increased bandwidth is required, Q m The lower the value, the better.
[0005] Therefore, in view of the shortcomings of the existing technology, it is very necessary to provide a potassium sodium niobate-based lead-free piezoelectric ceramic and its preparation method. Summary of the Invention
[0006] The first objective of this invention is to overcome the shortcomings of the prior art by providing a potassium sodium niobate-based lead-free piezoelectric ceramic. This potassium sodium niobate-based lead-free piezoelectric ceramic has a high mechanical quality factor, a good piezoelectric constant, and low dielectric loss, and has a wide range of applications.
[0007] The above-mentioned objectives of the present invention are achieved through the following technical measures:
[0008] A potassium sodium niobate-based lead-free piezoelectric ceramic is provided, with the chemical formula being:
[0009] 0.965K 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where 0 < x ≤ 0.04.
[0010] The raw materials for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic of the present invention include sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3).
[0011] The piezoelectric constant d of the potassium sodium niobate-based lead-free piezoelectric ceramic of the present invention 33 The mechanical quality factor is 292 pC / N to 320 pC / N; m The value is 153–235; the planar electromechanical coupling coefficient k p The dielectric constant tanδ is 0.50–0.55; the dielectric loss tanδ is 0.007–0.015; the Curie temperature T C The temperature ranges from 302℃ to 322℃.
[0012] The second objective of this invention is to overcome the shortcomings of the prior art by providing a method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics. The potassium sodium niobate-based lead-free piezoelectric ceramics prepared by this method possess high mechanical quality factor, good piezoelectric constant, and low dielectric loss, thus having a wide range of applications.
[0013] The above-mentioned objectives of the present invention are achieved through the following technical measures:
[0014] A method for preparing the above-mentioned potassium sodium niobate-based lead-free piezoelectric ceramic is provided, which is carried out through the following steps:
[0015] S1. Weigh out sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3) according to the stoichiometric ratio of the general chemical formula to obtain a mixture;
[0016] S2. Using anhydrous ethanol as a solvent, the mixture is ball-milled to obtain a mixed slurry;
[0017] S3. Dry and pre-calcine the mixed slurry to obtain dry powder;
[0018] S4. Add polyvinyl alcohol aqueous solution to the dry powder obtained in S3 and granulate, press and debind in sequence to obtain ceramic green body;
[0019] S5. The ceramic blank obtained in S4 is sintered to obtain a piezoelectric ceramic body;
[0020] S6. The piezoelectric ceramic body obtained in S5 is coated with a silver electrode and subjected to polarization treatment to obtain potassium sodium niobate-based lead-free piezoelectric ceramic.
[0021] In S2, ball milling is performed in a nylon jar, and the grinding media is zirconium balls.
[0022] In S3, the pre-firing temperature is 800℃~900℃, and the pre-firing time is 5h~7h.
[0023] In S4, the concentration of the polyvinyl alcohol aqueous solution is 6wt% to 8wt%.
[0024] In S5, the sintering temperature is 1060℃~1080℃, and the sintering time is 4h~6h.
[0025] In S6, the polarization voltage is 3kV / cm to 4kV / cm, and the polarization time is 10min to 20min.
[0026] This invention relates to a potassium sodium niobate-based lead-free piezoelectric ceramic and its preparation method, wherein the general chemical formula of the potassium sodium niobate-based lead-free piezoelectric ceramic is 0.965K. 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where 0 < x ≤ 0.04. The potassium sodium niobate-based lead-free piezoelectric ceramic of this invention does not contain lead, making it an environmentally friendly material. Furthermore, this potassium sodium niobate-based lead-free piezoelectric ceramic possesses a high mechanical quality factor, a good piezoelectric constant, and low dielectric loss, thus having a wide range of applications. Finally, the preparation method of this invention is simple, stable, easy to operate, and suitable for industrial production. Attached Figure Description
[0027] Figure 1 This is a schematic diagram showing the change in dielectric constant of the potassium sodium niobate-based lead-free piezoelectric ceramic of Example 1 as a function of temperature.
[0028] Figure 2 This is a schematic diagram showing the change in dielectric constant of the potassium sodium niobate-based lead-free piezoelectric ceramic of Example 2 as a function of temperature.
[0029] Figure 3 This is a schematic diagram showing the change in dielectric constant of the potassium sodium niobate-based lead-free piezoelectric ceramic of Example 3 as a function of temperature.
[0030] Figure 4 This is a schematic diagram showing the change in dielectric constant of the potassium sodium niobate-based lead-free piezoelectric ceramic of Example 4 as a function of temperature.
[0031] Figure 5 The impedance diagram is shown for the potassium sodium niobate-based lead-free piezoelectric ceramic of Example 1.
[0032] Figure 6 The impedance diagram is shown for the potassium sodium niobate-based lead-free piezoelectric ceramic of Example 2.
[0033] Figure 7 The impedance diagram is shown for the potassium sodium niobate-based lead-free piezoelectric ceramic of Example 3.
[0034] Figure 8 The impedance diagram is shown for the potassium sodium niobate-based lead-free piezoelectric ceramic of Example 4. Detailed Implementation
[0035] The technical solution of the present invention will be further described with reference to the following embodiments. Unless otherwise specified, the experimental methods in the following embodiments are conventional methods. Unless otherwise specified, the raw materials and reagents used in the following embodiments can be purchased from conventional biochemical reagent stores or pharmaceutical companies.
[0036] Example 1
[0037] A method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic with the general chemical formula 0.965K 0.45 Na 0.55 Nb (1-x) Ta xO3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where x = 0.01. The process is as follows:
[0038] S1. Weigh out sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3) according to the stoichiometric ratio of the general chemical formula to obtain a mixture;
[0039] S2. Using anhydrous ethanol as solvent and zirconium balls as milling media, the mixture was ball-milled in a nylon tank for 24 hours to obtain a mixed slurry.
[0040] S3. The mixed slurry is dried and pre-fired at a temperature of 850℃ for 6 hours to obtain dry powder.
[0041] S4. Add 7wt% polyvinyl alcohol aqueous solution to the dry powder obtained in S3 and granulate it sequentially. After granulation, use a mold with a diameter of 10mm to press it into small round pieces with a diameter of 10mm and a thickness of 1mm under a pressure of 10MPa. The ceramic body is obtained by arranging the adhesive side by side.
[0042] S5. The ceramic blank obtained in S4 is sintered at a temperature of 1060°C for 5 hours to obtain a piezoelectric ceramic body.
[0043] S6. The piezoelectric ceramic body obtained in S5 is coated with a silver electrode and polarized in silicone oil at 30°C. The polarization voltage is 4kV / cm and the polarization time is 15min, to obtain potassium sodium niobate-based lead-free piezoelectric ceramic.
[0044] Example 2
[0045] A method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic with the general chemical formula 0.965K 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where x = 0.02. The process is as follows:
[0046] S1. Weigh out sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3) according to the stoichiometric ratio of the general chemical formula to obtain a mixture;
[0047] S2. Using anhydrous ethanol as solvent and zirconium balls as grinding media, the mixture was ball-milled in a nylon tank for 24 hours to obtain a mixed slurry.
[0048] S3. The mixed slurry is dried and pre-fired at a temperature of 850℃ for 6 hours to obtain dry powder.
[0049] S4. Add 7wt% polyvinyl alcohol aqueous solution to the dry powder obtained in S3 and granulate it sequentially. After granulation, use a mold with a diameter of 10mm to press it into small round pieces with a diameter of 10mm and a thickness of 1mm under a pressure of 10MPa. The ceramic body is obtained by arranging the adhesive side by side.
[0050] S5. The ceramic blank obtained in S4 is sintered at a temperature of 1070°C for 5 hours to obtain a piezoelectric ceramic body.
[0051] S6. The piezoelectric ceramic body obtained in S5 is coated with a silver electrode and polarized in silicone oil at 30°C. The polarization voltage is 4kV / cm and the polarization time is 15min, to obtain potassium sodium niobate-based lead-free piezoelectric ceramic.
[0052] Example 3
[0053] A method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic with the general chemical formula 0.965K 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where x = 0.03. The process is as follows:
[0054] S1. Weigh out sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3) according to the stoichiometric ratio of the general chemical formula to obtain a mixture;
[0055] S2. Using anhydrous ethanol as solvent and zirconium balls as grinding media, the mixture was ball-milled in a nylon tank for 24 hours to obtain a mixed slurry.
[0056] S3. The mixed slurry is dried and pre-fired at a temperature of 800℃ for 5 hours to obtain dry powder.
[0057] S4. Add 6wt% polyvinyl alcohol aqueous solution to the dry powder obtained in S3 and granulate it sequentially. After granulation, use a mold with a diameter of 10mm to press it into small round pieces with a pressure of 10MPa. The pieces have a diameter of 10mm and a thickness of 1mm. The ceramic blanks are obtained by arranging the adhesive side by side.
[0058] S5. The ceramic blank obtained in S4 is sintered at a temperature of 1060°C for 6 hours to obtain a piezoelectric ceramic body.
[0059] S6. The piezoelectric ceramic body obtained in S5 is coated with a silver electrode and polarized in silicone oil at 30°C. The polarization voltage is 3kV / cm and the polarization time is 10min to obtain potassium sodium niobate-based lead-free piezoelectric ceramic.
[0060] Example 4
[0061] A method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic with the general chemical formula 0.965K 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where x = 0.04. The process is as follows:
[0062] S1. Weigh out sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3) according to the stoichiometric ratio of the general chemical formula to obtain a mixture;
[0063] S2. Using anhydrous ethanol as solvent and zirconium balls as grinding media, the mixture was ball-milled in a nylon tank for 24 hours to obtain a mixed slurry.
[0064] S3. The mixed slurry is dried and pre-fired at a temperature of 900℃ for 7 hours to obtain dry powder.
[0065] S4. Add 8wt% polyvinyl alcohol aqueous solution to the dry powder obtained in S3 and granulate it sequentially. After granulation, use a mold with a diameter of 10mm to press it into small round pieces with a pressure of 10MPa. The pieces have a diameter of 10mm and a thickness of 1mm. The ceramic blanks are obtained by arranging the adhesive side by side.
[0066] S5. The ceramic blank obtained in S4 is sintered at a temperature of 1080°C for 5 hours to obtain a piezoelectric ceramic body.
[0067] S6. The piezoelectric ceramic body obtained in S5 is coated with a silver electrode and polarized in silicone oil at 30°C. The polarization voltage is 3kV / cm and the polarization time is 20min to obtain potassium sodium niobate-based lead-free piezoelectric ceramic.
[0068] Comparative Example 1
[0069] A method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic with the general chemical formula 0.965K 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where x = 0.00. The process is as follows:
[0070] S1. Weigh out sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3) according to the stoichiometric ratio of the general chemical formula to obtain a mixture;
[0071] S2. Using anhydrous ethanol as solvent and zirconium balls as grinding media, the mixture was ball-milled in a nylon tank for 24 hours to obtain a mixed slurry.
[0072] S3. The mixed slurry is dried and pre-fired at a temperature of 850°C for 7 hours to obtain dry powder.
[0073] S4. Add 8wt% polyvinyl alcohol aqueous solution to the dry powder obtained in S3 and granulate it sequentially. After granulation, use a mold with a diameter of 10mm to press it into small round pieces with a pressure of 10MPa. The pieces have a diameter of 10mm and a thickness of 1mm. The ceramic blanks are obtained by arranging the adhesive side by side.
[0074] S5. The ceramic blank obtained in S4 is sintered at a temperature of 1060°C for 6 hours to obtain a piezoelectric ceramic body.
[0075] S6. The piezoelectric ceramic body obtained in S5 is coated with a silver electrode and polarized in silicone oil at 30°C. The polarization voltage is 3kV / cm and the polarization time is 20min to obtain potassium sodium niobate-based lead-free piezoelectric ceramic.
[0076] Comparative Example 2
[0077] A method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic with the general chemical formula 0.965K 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where x = 0.05. The process is as follows:
[0078] S1. Weigh out sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3) according to the stoichiometric ratio of the general chemical formula to obtain a mixture;
[0079] S2. Using anhydrous ethanol as solvent and zirconium balls as grinding media, the mixture was ball-milled in a nylon tank for 24 hours to obtain a mixed slurry.
[0080] S3. The mixed slurry is dried and pre-fired at a temperature of 900℃ for 6 hours to obtain dry powder.
[0081] S4. Add 8wt% polyvinyl alcohol aqueous solution to the dry powder obtained in S3 and granulate it sequentially. After granulation, use a mold with a diameter of 10mm to press it into small round pieces with a pressure of 10MPa. The pieces have a diameter of 10mm and a thickness of 1mm. The ceramic blanks are obtained by arranging the adhesive side by side.
[0082] S5. The ceramic blank obtained in S4 is sintered at a temperature of 1060°C for 6 hours to obtain a piezoelectric ceramic body.
[0083] S6. The piezoelectric ceramic body obtained in S5 is coated with a silver electrode and polarized in silicone oil at 30°C. The polarization voltage is 3kV / cm and the polarization time is 20min to obtain potassium sodium niobate-based lead-free piezoelectric ceramic.
[0084] Results Characterization and Performance Testing
[0085] 1. The dielectric constant as a function of temperature at a frequency of 100 kHz was tested using a high-temperature dielectric system.
[0086] Data on the relative permittivity of the potassium sodium niobate-based lead-free piezoelectric ceramics prepared in Examples 1 to 4 as a function of temperature at 100 kHz are shown below. Figures 1 to 4 As shown.
[0087] from Figures 1 to 4 It can be seen that the relative permittivity εr of all potassium sodium niobate-based lead-free piezoelectric ceramics exhibits two dielectric anomalous peaks as temperature changes. The first peak, occurring during the orthorhombic-tetragonal phase transition from low to high temperature, corresponds to the measured phase transition temperature T. O-T The first peak is between 70℃ and 80℃; the second peak is the dielectric anomalous peak that appears when transitioning from the tetragonal phase to the cubic phase. The phase transition temperature, i.e. the Curie temperature Tc, measured here is between 302℃ and 322℃, indicating a high Curie temperature.
[0088] 2. Impedance test
[0089] The impedance and phase angle curves as a function of frequency were measured using an impedance analyzer (HP 4294A).
[0090] Impedance testing was performed on the potassium sodium niobate-based lead-free piezoelectric ceramics prepared in Examples 1 to 4, as follows: Figures 5 to 8 As shown.
[0091] pass Figures 5 to 8 It can be seen that the potassium sodium niobate-based lead-free piezoelectric ceramics of the present invention can all obtain high phase angles. Specifically, the range is 86.6° to 88.7°, indicating more complete polarization and higher piezoelectric activity.
[0092] 3. Piezoelectric properties of potassium sodium niobate-based lead-free piezoelectric ceramics obtained in this invention
[0093] The potassium sodium niobate-based lead-free piezoelectric ceramics prepared in Examples 1 to 4 and Comparative Examples 1 and 2 of the present invention were utilized... 33 A piezoelectric tester (ZJ-3A) and an impedance analyzer (HP 4294A) were used to measure the piezoelectric constant d. 33 Planar electromechanical coupling coefficient k p Mechanical mass factor Q m Dielectric loss D and frequency constant N t As shown in Table 1.
[0094] Table 1. Piezoelectric performance data of potassium sodium niobate-based lead-free piezoelectric ceramics in Examples 1 to 4 and Comparative Examples 1 and 2.
[0095]
[0096] As can be seen from Examples 1 to 4 in the table above, when the Ta content is 0 < x ≤ 0.04, the piezoelectric constant and planar electromechanical coupling coefficient increase with the increase of Ta content, the mechanical quality factor and Curie temperature decrease with the increase of Ta content, and the dielectric loss and frequency constant increase slightly with the increase of Ta content, maintaining a relatively optimal value overall.
[0097] Comparative Examples 1 and 2 show that the overall performance is poor when the Ta content decreases to 0 or increases to 0.05%. At x = 0, the piezoelectric constant and planar electromechanical coupling coefficient drop sharply, while the mechanical quality factor and Curie temperature increase slightly, but not significantly. The dielectric loss increases slightly, and the frequency constant decreases slightly. At x = 0.05, the piezoelectric constant and planar electromechanical coupling coefficient are almost identical to those of the 0.04 composition, but the mechanical quality factor and Curie temperature decrease rapidly, while the dielectric loss and frequency constant increase slightly. Overall, the ceramic exhibits poor overall performance at x = 0 and x > 0.04, failing to meet practical application requirements.
[0098] In summary, the lead-free niobium-hafnium-zirconium-ferrite potassium sodium lithium bismuth copper piezoelectric ceramic of the present invention maintains a high mechanical quality factor while exhibiting high piezoelectric activity. Furthermore, it effectively increases the Curie temperature while possessing high piezoelectric performance, enabling its application over a wider temperature range. This lead-free niobium-hafnium-zirconium-ferrite potassium sodium lithium bismuth copper piezoelectric ceramic is an environmentally friendly material, conforming to the international sustainable development strategy and contributing to environmental protection.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic, characterized in that: The general chemical formula is 0.965K. 0.45 Na 0.55 Nb (1-x) Ta x O3-0.035Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO3-0.8%CuO-0.2%CuF2-0.3%Fe2O3, where 0<x≤0.04; The piezoelectric constant of the potassium sodium niobate-based lead-free piezoelectric ceramic d 33 The value is 292 pC / N to 320 pC / N; Mechanical quality factor Q m The range is 153 to 235; Planar electromechanical coupling coefficient k p It is 0.50 to 0.55; Dielectric loss tan δ The value ranges from 0.007 to 0.
015. Curie temperature T C The temperature ranges from 302℃ to 322℃. The preparation method is carried out through the following steps: S1. Weigh out sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3) according to the stoichiometric ratio of the general chemical formula to obtain a mixture; S2. Using anhydrous ethanol as a solvent, the mixture is ball-milled to obtain a mixed slurry; S3. Dry and pre-calcine the mixed slurry to obtain dry powder; S4. Add polyvinyl alcohol aqueous solution to the dry powder obtained in S3 and granulate, press and debind in sequence to obtain ceramic green body; S5. The ceramic blank obtained in S4 is sintered to obtain a piezoelectric ceramic body; S6. The piezoelectric ceramic body obtained in S5 is coated with a silver electrode and subjected to polarization treatment to obtain potassium sodium niobate-based lead-free piezoelectric ceramic. In S5, the sintering temperature is 1060℃~1080℃, and the sintering time is 4h~6h.
2. The method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics according to claim 1, characterized in that: The raw materials for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic include sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), bismuth trioxide (Bi2O3), zirconium oxide (ZrO2), copper oxide (CuO), copper fluoride (CuF2), and ferric oxide (Fe2O3).
3. The method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics according to claim 1, characterized in that: In S2, ball milling is performed in a nylon jar, and the grinding media is zirconium balls.
4. The method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics according to claim 1, characterized in that: In S3, the pre-firing temperature is 800℃~900℃, and the pre-firing time is 5h~7h.
5. The method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics according to claim 1, characterized in that: In S4, the concentration of the polyvinyl alcohol aqueous solution is 6wt% to 8wt%.
6. The method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics according to claim 1, characterized in that: In S6, the polarization voltage is 3 kV / cm to 4 kV / cm, and the polarization time is 10 min to 20 min.
Citation Information
Patent Citations
Potassium-sodium niobate-based leadless piezoelectric ceramic and preparation method thereof
CN111302797A